Peran Mahasiswa KKN UINSU terhadap Pemberantasan Buta Huruf al Qur'an dan Isu Stunting pada Masyarakat di Desa Batu Gemuk Kec. Namorambe Kab. Deli Serdang - Muhammad Fachri Sitompul; Faridah Yafizham; Ajizah Nur Ismail Berutu; Nuh Ahmad Syarodzi Ritonga; Alwi Padly Harahap (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Indonesia is a developing country which consists of many islands and has a middle to lower economic system. This results in the quality of life of the community, such as being vulnerable to stunting and having less education, such as the number of children who are illiterate in the Qur'an. The purpose of this study was to determine the role of KKN 210 students in eliminating illiteracy in the Qur'an in children and counseling related to stunting. This research method uses descriptive qualitative analysis. The results of this study indicate that students have a role and participate in eliminating illiteracy of the Qur'an in children in Batu Gemu village by opening opportunities for children to learn to read the Qur'an openly which is carried out in a mosque which is in the village. In addition, students also have a role in stunting education, the purpose of which is to provide awareness for the community to always pay attention to cleanliness and child nutrition. The counseling has an effect on parents' understanding of the dangers of stunting in children.